(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The occupation of urban landscapes by birds and their adaptation to living there is a continuous evolutionary process. Especially in recent years, the activities of synanthropic species in urban landscapes have played a role in causing certain environmental pollution issues, making it crucial to identify the ecological factors that determine the species composition, distribution, and population size of these species. This knowledge can help optimize the relationship between humans and birds.